Dual band low-noise amplifier designs for bluetooth and hiperLAN applications - Mou, Shouxian (2008)
The investigation on the designs of dual-band LNAs, as well as a modified architecture used for input matching in CMOS LNAs to make the circuit more compact, is presented in this thesis. According to the proposed investigation, a narrow-band LNA (LNA1), a wideband LNA (LNA3) and two dual-band LNAs (LNA4 and LNA5) are designed with CSM 0.18µm CMOS technology. The corresponding design considerations are also presented in detail in the thesis. The thesis provides an approach which can help to achieve a compact and fully-integrated LNA.